A double‐blind, placebo‐controlled trial on the antihypertensive treatment effect of a quadruple single‐pill combination. Issue 4 (6th February 2021) - Hu, Lei‐Xiao; Wang, Dian; Liu, Hua‐Ling; Zhang, Qing‐Tao; Sun, Dong‐Sheng; Zhang, Li; Chen, Xin; Chang, Gui‐Li; Wang, Ji‐Guang
Abstract: In a randomized, double‐blind, placebo‐controlled trial, we investigated antihypertensive treatment effect of a quadruple single‐pill combination of reserpine 0.1 mg, dihydralazine 12.5 mg, hydrochlorothiazide 12.5 mg, and triamterene 12.5 mg, and changes in plasma levels of monoamine neurotransmitters (serotonin, norepinephrine, and dopamine) in patients with grade 1 hypertension. Eligible patients with a systolic/diastolic blood pressure (BP, average of six readings at two clinic visits during a 4‐week run‐in period) of 140‐159/90–99 mmHg were randomly assigned to the quadruple combination ( n = 30) or placebo ( n = 30). The randomized patients were instructed to take a pill of the combination or placebo once daily and followed up at 4, 8, and 12 weeks, respectively. Monoamine neurotransmitters were measured at baseline and 12 weeks of follow‐up. After 12‐week treatment, systolic/diastolic BP significantly ( p ≤ .0001) decreased from 140.8 ± 7.9/89.5 ± 7.5 mmHg at baseline by 9.8 ± 1.8/6.4 ± 1.3 mmHg in the combination group. The corresponding values in the placebo group were 141.3 ± 7.9/90.3 ± 7.3 mmHg and 5.2 ± 1.8/0.4 ± 1.3 mmHg, respectively. The between‐group differences in systolic/diastolic BP changes were −4.6/−6.0 mmHg (95% CI, −9.7 to 0.6/−9.7 to −2.2 mmHg, p ≤ .08). The control rate of hypertension was higher in the combination than placebo group (63.3% vs. 16.7%, p = .0002). Plasma serotonin, but not norepinephrine or dopamine, changed in both treatment and placebo groups ( p ≤ .01). Nonetheless, plasma norepinephrine tended to decrease in the treatment group (−34.4 pg/ml, p = .09). Adverse events occurred in 5 (16.7%) and 3 (10.0%) patients in the combination and placebo groups, respectively. Our study showed that the quadruple combination reduced BP and caused some changes in plasma neurotransmitters.